The Cholinergic Lateral Line Efferent Synapse: Structural, Functional and Molecular Similarities With Those of the Cochlea - Plazas, Paola V.; Elgoyhen, Ana Belén (Frontiers in Cellular Neuroscience, 2021)
Vertebrate hair cell (HC) systems are innervated by efferent fibers that modulate their response to external stimuli. In mammals, the best studied efferent-HC synapse, the cholinergic medial olivocochlear (MOC) efferent system, makes direct synaptic contacts with HCs. The net effect of MOC activity is to hyperpolarize HCs through the activation of α9α10 nicotinic cholinergic receptors (nAChRs) and the subsequent activation of Ca2+-dependent SK2 potassium channels. A serious obstacle in research on many mammalian sensory systems in their native context is that their constituent neurons are difficult to access even in newborn animals, hampering circuit observation, mapping, or controlled manipulation. By contrast, fishes and amphibians have a superficial and accessible mechanosensory system, the lateral line (LL), which circumvents many of these problems. LL responsiveness is modulated by efferent neurons which aid to distinguish between external and self-generated stimuli. One component of the LL efferent system is cholinergic and its activation inhibits LL afferent activity, similar to what has been described for MOC efferents. The zebrafish (Danio rerio) has emerged as a powerful model system for studying human hearing and balance disorders, since LL HC are structurally and functionally analogous to cochlear HCs, but are optically and pharmacologically accessible within an intact specimen. Complementing mammalian studies, zebrafish have been used to gain significant insights into many facets of HC biology, including mechanotransduction and synaptic physiology as well as mechanisms of both hereditary and acquired HC dysfunction. With the rise of the zebrafish LL as a model in which to study auditory system function and disease, there has been an increased interest in studying its efferent system and evaluate the similarity between mammalian and piscine efferent synapses. Advances derived from studies in zebrafish include understanding the effect of the LL efferent system on HC and afferent activity, and revealing that an α9-containing nAChR, functionally coupled to SK channels, operates at the LL efferent synapse. In this review, we discuss the tools and findings of these recent investigations into zebrafish efferent-HC synapse, their commonalities with the mammalian counterpart and discuss several emerging areas for future studies.